Unnecessary bilateral salpingo-oophorectomy at the time of hysterectomy and potential for ovarian preservation. Issue 1 (January 2021) - Wong, Jellena; Murji, Ally; Sunderji, Zahra; Chow, Ovina; Shapiro, Jodi; Wolfman, Wendy; Shirreff, Lindsay
Abstract: Objective: To evaluate predictors of bilateral salpingo-oophorectomy at hysterectomy and determine rate of unnecessary bilateral salpingo-oophorectomy. Methods: Retrospective review of hysterectomies at six Ontario, Canada hospitals from July 2016 to June 2018. Data was extracted from health records coding and electronic medical records. Of patients with concurrent bilateral salpingo-oophorectomy, age, preoperative diagnoses, surgical factors (presence of endometriosis/adhesions), and surgeon training (fellowship/no fellowship) were recorded. Chi-square tests compared indicated and nonindicated bilateral salpingo-oophorectomy cases based on preoperative diagnosis. Criteria for unnecessary bilateral salpingo-oophorectomy were: age under 51 years, benign preoperative diagnosis, and absence of intraoperative endometriosis and adhesions. Results: Concurrent bilateral salpingo-oophorectomy occurred in 749/2, 656 (28%) cases with 509/749 (68%) indicated based on preoperative diagnosis. There was interhospital variation in rate of indicated bilateral salpingo-oophorectomy based on preoperative diagnosis (45.3%–76.9%, χ 2 P  < 0.001). Concurrent bilateral salpingo-oophorectomy at academic centers was more likely to have preoperative indications versus those at community hospitals (70% vs 63%, OR 1.42, 95% CI 1.02–1.97, P  = 0.04). BSO performed by fellowship-trained surgeons were more likely to be indicated than those performed by generalists (75% vs 63%, OR 1.76, 95% CI 1.26–2.44, P  = 0.001). Of patients without preoperative indications for bilateral salpingo-oophorectomy, 105/239 (44%) were under 51 years of age, of which 59 (58%) had no intraoperative endometriosis/adhesions. Ovarian preservation may have been reasonable in 8% (59/749). Conclusions: Concurrent bilateral salpingo-oophorectomy performed by generalists and at community hospitals was less likely to have preoperative indications. Ovarian preservation was potentially possible for 8%.